2010
DOI: 10.1111/j.1740-8261.2009.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Liposomal Doxorubicin and Daily Palliative Radiotherapy in Advanced Feline Soft Tissue Sarcomas

Abstract: Local recurrence of feline soft tissue sarcomas is common despite aggressive treatment. Liposomal doxorubicin might serve as a depot radiosensitizer if administered concomitantly with daily radiotherapy and thus improve tumor control. In this pilot study, the feasibility of concomitant liposomal radiochemotherapy was evaluated in a palliative setting in 10 cats with advanced soft tissue sarcomas. Cats were treated with median number of 5 (range 5-7) daily fractions of radiotherapy and a median total dose of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…In a pilot study including 10 cats with advanced FISS, it was shown that liposomal doxorubicin used with palliative daily fraction radiotherapy could also be used as a depot radiosensitizer [37]. Additionally, in a study performed on 12 cats with non-resectable FISS, combining doxorubicin with cyclophosphamide resulted in a partial response in 50% of cats and significant improvement in the survival time of responders [38].…”
Section: Search Strategymentioning
confidence: 99%
“…In a pilot study including 10 cats with advanced FISS, it was shown that liposomal doxorubicin used with palliative daily fraction radiotherapy could also be used as a depot radiosensitizer [37]. Additionally, in a study performed on 12 cats with non-resectable FISS, combining doxorubicin with cyclophosphamide resulted in a partial response in 50% of cats and significant improvement in the survival time of responders [38].…”
Section: Search Strategymentioning
confidence: 99%
“…Despite observable increases of drug levels at tumour sites, the clinical outcomes of human patients treated with liposome-encapsulated Doxorubicin have been the same as those treated with free Doxorubicin [15, 16]. The low response rate of these liposomal formulations was purported to be due to a lack of understanding of drug release from the liposomes [17]. …”
Section: Liposomes As Delivery Platformsmentioning
confidence: 99%
“…Due to liposome-based drugs having longer in vivo circulations, sensitizing agents can be loaded into liposomes to serve as potent pretreatment sensitizers for radiotherapy in cancer. A study conducted in 2010 demonstrated improved therapeutic outcomes in cats with advanced feline soft tissue sarcomas when given liposomal Doxorubicin concomitantly with daily palliative radiotherapy [17]. Liposomal Doxorubicin has been shown to sensitize tumour cells to concomitantly administered radiotherapy [17].…”
Section: Liposomes As Delivery Platformsmentioning
confidence: 99%
See 2 more Smart Citations